Two cases of unilateral limbal Vernal keratoconjunctivitis in the same family: first case report - Michieletto, Paola; Sica, Attilio; Barbi, Egidio; Pensiero, Stefano (Frontiers in Pediatrics, 2023)
This case report describes two cases of unilateral limbal Vernal keratoconjunctivitis (VKC) in the same family. To our knowledge, these are the first two reported cases of unilateral limbal VKC. VKC is a chronic inflammatory disease that typically affects both eyes, with unilateral cases being rare and previously only reported in the tarsal form. Our first case involved a 12-year-old girl with a history of allergic asthma, who had been experiencing conjunctivitis in her right eye since the age of 7. Upon examination, she was diagnosed with unilateral limbal VKC and treated with 1% cyclosporine eye drops with a significant improvement observed at the one and three-month follow-ups. Her 7-yearold brother was also examined and found to have unilateral limbal VKC in his right eye, although it was milder and not associated with allergic pathogenesis. Therefore, in this case, a treatment with hydrocortisone eye drops was started leading to an immediate reduction of the itching. In both cases an IgE-mediated mechanism is less likely because of the monolateral eye involvement, the complete absence of nasal symptoms, the lack of correlation between symptoms and any pollen season, and the negative prick skin test in one of the two siblings. Both cases suggest that unilateral VKC may occur even in the limbal form and that genetic mechanisms may contribute to the inflammatory reaction in VKC. This report highlights the need for further studies to explain the occurrence of unilateral VKC cases and reminds clinicians to consider the possibility of unilateral limbal VKC in pediatric patients.